Mikuš, Julie, Josef, Katka, Petr, Klárka, Karel, Irena, Hana, Rudolf, Marie, Alenka, Ladislav, David, Adélka-- - Fuchsová, Irena, 1950- (Beskydy, 2014)
Čtěte, a uvidíte, co prožije desetiletý Mikuš Kopřiva z Kolína, od 5. prosince 2012 do 5. listopadu 2013.